2021
DOI: 10.3892/ijo.2021.5266
|View full text |Cite
|
Sign up to set email alerts
|

LINC00514 promotes lipogenesis and tumor progression in esophageal squamous cell carcinoma by sponging miR‑378a‑5p to enhance SPHK1 expression

Abstract: Increasing evidence has demonstrated that long non-coding RNAs serve pivotal roles in tumor development, progression, metastasis and metabolism. However, to the best of our knowledge, the roles and molecular mechanisms of long intergenic nonprotein-coding RNA 00514 (LINC00514) in esophageal squamous cell carcinoma (ESCC) remain unknown. The present study found that LINC00514 and sphingosine kinase 1 (SPHK1) were both upregulated in ESCC tissues and cells, and their high expression levels were closely associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 56 publications
1
8
0
1
Order By: Relevance
“…Another study demonstrated that LINC00514 in the nucleus of papillary thyroid cancer cells promotes tumor progression by elevating CD23 expression [ 14 ]. Similar trends have been reported in tumors, such as cervical cancer [ 15 ], triple-negative breast cancer [ 16 , 17 ], osteosarcoma [ 18 ], and esophageal cancer [ 19 ], but not in NSCLC.…”
Section: Introductionsupporting
confidence: 77%
“…Another study demonstrated that LINC00514 in the nucleus of papillary thyroid cancer cells promotes tumor progression by elevating CD23 expression [ 14 ]. Similar trends have been reported in tumors, such as cervical cancer [ 15 ], triple-negative breast cancer [ 16 , 17 ], osteosarcoma [ 18 ], and esophageal cancer [ 19 ], but not in NSCLC.…”
Section: Introductionsupporting
confidence: 77%
“…126 LINC00514, acting as a ceRNA, upregulates SPHK1 by sponging miR-378a-5p and activates adipogenesisrelated pathways, thereby promoting the proliferation and invasion of ESCC cells. 127 In a RMS-derived cell line, miR-378a upregulation inhibited IGF1R expression and impacted phosphorylated-Akt protein levels. 51 Moreover, ectopic expression of miR-378a modulated apoptosis, cell migration, cytoskeleton organization, and the expression of the muscle markers MyoD1, MyoR, desmin, and MyHC in RMS.…”
Section: Other Cancersmentioning
confidence: 99%
“… 126 LINC00514, acting as a ceRNA, upregulates SPHK1 by sponging miR-378a-5p and activates adipogenesis-related pathways, thereby promoting the proliferation and invasion of ESCC cells. 127 …”
Section: Upregulation Of Mir-378a Promotes Malignant Transformation A...mentioning
confidence: 99%
“…Cytoplasmic lncRNAs can competitively bind miRNAs and regulate miRNA target genes at the posttranscriptional level (8). A large amount of literature has shown that lncRNAs play a regulatory role in the development of ESCC (9)(10)(11). In this study, the differentially expressed lncRNA FOXP4-AS1 was screened by the microarrays.…”
Section: Introductionmentioning
confidence: 99%